Layer-by-layer assembly of nanorods on a microsphere via electrostatic interactions. Issue 22 (11th May 2018) - Zhang, Liuyang; Zhu, Lu; Larson, Steven R.; Zhao, Yiping; Wang, Xianqiao
Abstract : Combining coarse-grained molecular dynamics simulations and experiments, a systematic study on both the dynamics and equilibrium behavior of the layer-by-layer (LbL) assembly of charged nanorods (NRs) onto a charged microsphere (MS) via electrostatic interactions has been carried out. Abstract : Combining coarse-grained molecular dynamics simulations and experiments, a systematic study on both the dynamics and equilibrium behavior of the layer-by-layer (LbL) assembly of charged nanorods (NRs) onto a charged microsphere (MS) via electrostatic interactions has been carried out. The adsorption of the first layer of NRs on the MS follows a growth-saturation dynamics. The adsorption rate is governed by a diffusion limited process when the NR concentration ( C NR ) is low, while the rate is independent of C NR when C NR is high. The equilibrium NR coverage on the microsphere is found to follow a Langmuir adsorption model. For multilayer LbL assembly, when C NR is low, the number ( N ) of NRs adsorbed onto the MS follows a linear relationship with the number of dips M ; while when C NR is high, in each dip the MS surface is fully covered with NRs, and the N follows a quadratic relationship with M . Most simulation results have been confirmed by experiments using α-Fe2 O3 NRs and magnetic microspheres modified by poly(diallyldimethylammonium chloride) and poly(styrenesulfonate, sodium salt). These findings provide useful guidelines for designing complex superparticles via charged building nanoblocks based on electrostatic interactions, and therefore open up a novel avenue to exploit the capability of self-assembled charged nanostructures for potential applications such as surface modifications, sensors, drug delivery vehicles, etc.